#OculoplasticsandSocialMedia: a review of social media in oculoplastics and relevant subspecialties. (4th March 2022) - Tingley, Jennifer; Allen, Richard C.; Barmettler, Anne
ABSTRACT: The permeation of social media into life almost goes without bounds and medicine is no exception. While social media holds great potential for physicians and medicine, it also comes with concurrent spread of disinformation. This increases the importance of evidence-based information from qualified physicians on social media. Although the definition of social media is broad, in general, it refers to the use of web-based platforms to connect one human to another. In oculoplastic surgery, these relationships can be physician to physician, physician to patient, patient to patient, and vendor to physician. These relationships mostly involve education, social support, and advertising, but can also include research and government advocacy. The purpose of this review is to evaluate the current utilization of social media in oculoplastic surgery and relevant subspecialties.